Health Law and Medical Ethics : Implications in the use of Psychotropics Drugs - Fikri , Ahmad Ma'mun; Fahrudin, Aziz; Wardani, Dita Nur (Journal of Law, Politic and Humanities, 2025)
In medical practice, the application of medical ethics often overlaps with general societal ethics, particularly in the use of psychotropic drugs. Regulations related to psychotropics have been established in various legal provisions, such as the Health Law and the Psychotropics Law, to ensure the safe and controlled use of these substances. However, in practice, there are still instances of abuse of authority by medical personnel, including improper prescription procedures and unlawful distribution. This study employs a normative juridical method, utilizing a legislative and conceptual approach. The findings indicate that legal sanctions for such violations have been established, including criminal and administrative penalties. However, the implementation of these sanctions still faces challenges in terms of effectiveness and balancing patient protection with access to medication. From a medical ethics perspective, the principles of beneficence, non-maleficence, and informed consent must be upheld in prescribing these drugs to protect patients' rights and prevent dependency or harmful side effects. Therefore, a more comprehensive policy evaluation is necessary to ensure the proper use of psychotropic drugs in accordance with legal and ethical principles while strengthening oversight in medical practice to prevent misuse.